Applying Total Quality Management principles in Non-Governmental Organizations, Case Study of Nablus & Ramallah - Sairafy, Balsam; Awad, Marah (My University, 2020)
This project aims to study the extent to which the principles of total quality are applied in institutions in foreign and local non-governmental organizations operating in both Ramallah and Nablus. This mission also seeks to identify the reality of applying the principles of total quality in foreign and local non-governmental institutions, and to identify the performance measures that these institutions follow. In order to achieve the objectives of this study, a questionnaire was designed that aims at the field study of problem variables the study is in order to test the hypotheses, so that the study population consists of workers in higher management (Director of the institution, deputy director) in foreign and local (civil) institutions and non-governmental organizations that operate in (Ramallah and Nablus). (150) questionnaires were distributed to the study sample retrieving (112) questionnaires, i.e. a rate of (74.66%). The study concluded that there is a great deal of interest on the part of foreign NGOs working in. It is based on the principles of total quality, and the application of these variables in degrees and levels varying positive, it was the highest level of application share focus on customers and audience beneficiaries. The study also found that there is a great interest from these institutions in the institutional performance for its departments and tasks, and striving to improve, develop and apply these variables to degrees and positive levels varying by achieving the satisfaction of the institution, customers, workers and society. The study also showed that there is a statistically significant relationship between all the variables of quality principles the comprehensive study adopted by the researcher and the institutional performance followed in those non-governmental institutions. The study extracted several recommendations, the most important of which are: The need for increased attention and commitment to management institutions have applied all the dimensions of comprehensive quality and its impact on the development of their own institutional performance, and the need to involve workers in making decisions related to quality in order to provide better quality service to customers. The message also extracted the necessity of having flexible administrative systems that facilitate the provision of services with the required quality and speed, as well as increased attention. To develop its institutional performance